(untitled) (The Planet, 2024)
Introduction: Globally, preeclampsia stands as a primary contributor to maternal and perinatal morbidity and mortality. This hypertensive disorder typically manifests after 20 weeks of gestation and exhibits a higher prevalence in low and middle-income nations. Aim of the study: This study aimed to assess the prevalence and risk factors of preeclampsia among pregnant women. Methods and materials: This hospital-based cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Dhaka Medical College and Hospital, Dhaka, Bangladesh from January 2021 to December 2021. As the study subjects, a total of 77 pregnant women who delivered at the gestational age of 28 weeks and above were enrolled by using a purposive sampling technique. For data analysis, SPSS version 23.0 was applied. Results: In this study, a notable 24.7% frequency of preeclampsia was observed among the participants. In the analysis of risk factors, family history of high blood pressure, household smoking, gravity >2, and serum calcium level (mg/dl) lower than normal were identified as statistically significant predictive factors. The P-values for these factors were found to be <0.001, 0.001, 0.002, and <0.001 respectively, in Odds ratio calculations and/or Student’s T-tests. Conclusion: Approximately one-fourth of pregnant women in Bangladesh face the risk of developing preeclampsia. The potential contributors to these cases include a family history of high blood pressure and household smoking.